-(5x-7)-(4x-4)+8=-8(x-3)-(8x+9)+8

Simple and best practice solution for -(5x-7)-(4x-4)+8=-8(x-3)-(8x+9)+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(5x-7)-(4x-4)+8=-8(x-3)-(8x+9)+8 equation:


Simplifying
-1(5x + -7) + -1(4x + -4) + 8 = -8(x + -3) + -1(8x + 9) + 8

Reorder the terms:
-1(-7 + 5x) + -1(4x + -4) + 8 = -8(x + -3) + -1(8x + 9) + 8
(-7 * -1 + 5x * -1) + -1(4x + -4) + 8 = -8(x + -3) + -1(8x + 9) + 8
(7 + -5x) + -1(4x + -4) + 8 = -8(x + -3) + -1(8x + 9) + 8

Reorder the terms:
7 + -5x + -1(-4 + 4x) + 8 = -8(x + -3) + -1(8x + 9) + 8
7 + -5x + (-4 * -1 + 4x * -1) + 8 = -8(x + -3) + -1(8x + 9) + 8
7 + -5x + (4 + -4x) + 8 = -8(x + -3) + -1(8x + 9) + 8

Reorder the terms:
7 + 4 + 8 + -5x + -4x = -8(x + -3) + -1(8x + 9) + 8

Combine like terms: 7 + 4 = 11
11 + 8 + -5x + -4x = -8(x + -3) + -1(8x + 9) + 8

Combine like terms: 11 + 8 = 19
19 + -5x + -4x = -8(x + -3) + -1(8x + 9) + 8

Combine like terms: -5x + -4x = -9x
19 + -9x = -8(x + -3) + -1(8x + 9) + 8

Reorder the terms:
19 + -9x = -8(-3 + x) + -1(8x + 9) + 8
19 + -9x = (-3 * -8 + x * -8) + -1(8x + 9) + 8
19 + -9x = (24 + -8x) + -1(8x + 9) + 8

Reorder the terms:
19 + -9x = 24 + -8x + -1(9 + 8x) + 8
19 + -9x = 24 + -8x + (9 * -1 + 8x * -1) + 8
19 + -9x = 24 + -8x + (-9 + -8x) + 8

Reorder the terms:
19 + -9x = 24 + -9 + 8 + -8x + -8x

Combine like terms: 24 + -9 = 15
19 + -9x = 15 + 8 + -8x + -8x

Combine like terms: 15 + 8 = 23
19 + -9x = 23 + -8x + -8x

Combine like terms: -8x + -8x = -16x
19 + -9x = 23 + -16x

Solving
19 + -9x = 23 + -16x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '16x' to each side of the equation.
19 + -9x + 16x = 23 + -16x + 16x

Combine like terms: -9x + 16x = 7x
19 + 7x = 23 + -16x + 16x

Combine like terms: -16x + 16x = 0
19 + 7x = 23 + 0
19 + 7x = 23

Add '-19' to each side of the equation.
19 + -19 + 7x = 23 + -19

Combine like terms: 19 + -19 = 0
0 + 7x = 23 + -19
7x = 23 + -19

Combine like terms: 23 + -19 = 4
7x = 4

Divide each side by '7'.
x = 0.5714285714

Simplifying
x = 0.5714285714

See similar equations:

| 2l-3y=36-6y | | 3k-4/2=5 | | 3b-5=2b+1 | | 16x+15=4x-9 | | 6y+1=61 | | -3x/4+1=7/12 | | 3x-3y=27 | | 3y+2y+y= | | x^2+xy+y^2=7 | | 8(1+w)=7(8+w) | | 5z-1=z+7 | | 7(x-3)-(6-2x)=-3x-2(5-x) | | 7x-11-4x=5x-8 | | 2msquared+1=19 | | (x+2)(x-2)=35 | | -4a+6+5a=15-22 | | 3x+2-3=8 | | -12/3(-8+(-4)^2-6)+2 | | 2m+1=19 | | 9x^3-36x^2+20x= | | 5/6x-1/2=-2 | | 16x-9=-8 | | 5(x+4)=9x+5-4x+15 | | 4-n=3n | | 6(z-6)-(9-5z)=10z | | 0=400-16t^2 | | 2x-(6y+2x)= | | 0.6(y-3)=0.1y | | 7z+10-5z=8+z+6 | | 3k/4=11/8 | | 20y-75=25 | | 0.4x-5=0.1(x+10) |

Equations solver categories